MY GUMMY DAN SOESANG MILK: TREN PEMANFAATAN SUSU DAN BUAH LOKAL SEBAGAI INOVASI GUNA MENDONGKRAK UMKM - Prapanca, Detak; Musyarofah, Sitta Rifatul; Maharani R.A, Viola; Sabela, Eka; Ismi W, Melly Wanda (Universitas Kadiri, 2024)
Gendro is a village in Pasuruan, East Java, which is rich in dairy milk potential and local fruits such as oranges. Through this potential, the KKN-P group consisting of 69 UMSIDA students innovated to develop products made from milk and oranges which became the flagship of Gendro village in the form of orange jelly candy branded